Integrated photonic devices for realizing photonic quantum computing: part 1: FDTD (quantum devices) - Muhammad Faris Zikri Bin Zainal (Nanyang Technological University, 2024)
The search for viable quantum computing systems has prompted the investigation of several platforms, with photonic devices showing great promise. To advance photonic quantum computing, this report focuses on the usage of integrated photonic devices, namely beam splitters functioning as directional couplers. The first section of the report introduces the essential ideas behind photonic quantum computing and emphasizes the significance of integrated photonic devices in this context. The details of beam splitters as directional couplers and their significant function in quantum computing activities are then covered in detail. The finite-difference time-domain (FDTD) approach is a useful tool for simulating quantum systems, and it is covered in detail in this research. With an emphasis on FDTD's use in integrated photonic devices, the paper examines both its advantages and disadvantages, opening the door to more thorough simulations of quantum circuits.